Compact 3D Metal Collectors Enabled by Roll‐to‐Roll Nanoimprinting for Improving Capacitive Energy Storage. Issue 4 (2nd February 2022) - Zheng, Qinwen; Li, Xiangming; Yang, Qingzhen; Li, Congming; Wu, Lifeng; Wang, Yingche; Sun, Pengcheng; Tian, Hongmiao; Wang, Chunhui; Chen, Xiaoliang; Shao, Jinyou
Abstract: Reducing the contact resistance between active materials and current collectors is of engineering importance for improving capacitive energy storage. 3D current collectors have shown extraordinary promise for reducing the contact resistance, however, there is a major obstacle of being bulky or inefficient fabrication before they become viable in practice. Here a roll‐to‐roll nanoimprinting method is demonstrated to deform flat aluminum foils into 3D current collectors with hierarchical microstructures by combining soft matter‐enhanced plastic deformation and template‐confined local surface nanocracks. The generated 3D current collectors are inserted by and interlocked with active electrode materials such as activated carbon, decreasing the contact resistance by at least one order of magnitude and quadrupling the specific capacitance at high current density of 30 A g –1 for commercial‐level mass loading of 5 mg cm –2 . The 3D current collectors are so compact that they have a low volume percentage of 7.8% in the entire electrode film, resulting in energy and power density of 29.1 Wh L –1 and 12.8 kW L –1, respectively, for stack cells in organic electrolyte. Furthermore, roll‐to‐roll nanoimprinting of metal microstructures is low‐cost, high‐throughput, and can be extended to other systems that involve the microstructured metal interface, such as batteries and thermal management. Abstract : A roll‐to‐roll nanoimprinting method is applied to deform flat aluminum foils into 3D current collectors with hierarchical microstructures. The 3D current collector reduces the contact resistance by an order of magnitude and comprehensively improves the electrochemical performance of the supercapacitor. The method can be extended to other systems that involve the microstructured metal interface, such as batteries and thermal management.